The role of alkaline activator in geopolymerization process of Low-calcium fly ash based geopolymers - Abdul Kareem, Omar A.K.A (School of Materials Engineering, 2010)
The main purpose of the research was to study the effect of the alkaline activator content and the alkaline activator constituents (Waterglass and NaOH solution) mixing ratio, on the compressive strength and on the microstructure of the resulted low- calcium (Class F) Fly ash-based geopolymer.